Organ-specific effects on inflammation and apoptosis of recombinant human activated protein C in a murine model of sepsis. (August 2017) - Simon, Tim-Philipp; Mueckenheim, Hendrik; Wagner, Tobias; Sponholz, Christoph; Claus, Ralf Alexander; Saenger, Joerg; Marx, Gernot; Schuerholz, Tobias
There is legitimate interest in the effects of recombinant human activated protein C (rhAPC) on various organs and individual patients, but the specific effects on organ tissues during early sepsis remain unknown. Differences in the levels of organ damage may influence responses to drug therapy. We aimed to investigate whether rhAPC induces organ-specific effects on inflammation and apoptosis using randomized, experimental trials with male NMRI mice. Animals underwent caecal ligation and puncture, and after 12 h, sepsis inflammation and apoptosis were assessed by plasma cytokines, gene expression ratios and immunohistochemistry (IHC). RhAPC-treated animals exhibited increased physical activity and decreased cytokine release compared to untreated animals (interleukin-6 reduction 58%, P < 0.001). CD14 expression was higher in the heart and liver and decreased upon rhAPC application in the heart (−35%), liver and kidney (both −60%). Macrophage inflammatory protein 2 (MIP2) expression decreased in the heart (−58%) but not in the liver or kidney. IHC revealed decreased cleaved caspase-3 in the heart and kidney due to rhAPC intervention. Preservation of the endothelial PC receptor was significant only in the heart during sepsis ( P = 0.007). In early polymicrobial sepsis, inflammation was more pronounced in the heart and liver compared to the kidney. RhAPC exhibited protective effects, especially in the heart tissue, and led to reduced plasma levels of pro-inflammatory cytokines and improved physical activity.